Special Protective Regimes of Administrative Law and States of Emergency. Fundamental Problems of Delimitation and Constitutional Standards of Limiting the Freedoms and Rights of Individuals - Kamiński, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of the considerations is the issue of special protective regimes of administrative law as a qualified type of special order of administrative law regulation applicable in situations of threats to significant legal goods of a collective nature. The purpose of the analysis is to present the relationship of such regimes to the extraordinary states (martial law, state of emergency, state of natural disaster) and to the constitutional limits of statutory restriction of the freedoms and rights of individuals during the period when the norms belonging to these regimes are in force or applied. Particular attention was paid to the issues of regimes related to the occurrence of an epidemic, an epidemic threat and a radiation emergency. The study also takes into account the issues of new categories of special regimes (qualified protection zones in the area of the states of epidemic or epidemic threat and the area of the prohibition of staying in the border zone).